Characterization on surface modification of kenaf biomass via microbial fermentation - M.I, Ahmad Fitrie; Anuar, Hazleen; Mohd Nordin, Nur Aisyah; Mohd Nasir, Nur Aimi; Seeni Mohamed, Nurhafizah; Mel, Maizirwan; Othman, Rashidi; Abd Razak, Shamsul Bahri (Trans Tech Publications, Switzerland, 2012)
Kenaf is categorized as one of the natural fibre which is used as replacement to manmade fibre due to its various advantages. It is a natural fibre of low density, low cost, recyclable and biodegradable. This paper presents the surface modification of kenaf biomass in terms of its morphology, chemical properties and crystallinity, as observed under scanning electron microscope (SEM), Fourier transform infrared (FTIR) and X-ray diffraction (XRD), respectively. Peak at 1600 cm-1 to 1200 cm-1 FTIR shows the disappearance of lignin in the treated kenaf. On the other hand, crystallinity indexes (CI) for untreated and treated kenaf are determined by XRD that show 83.3 % and 67.7 % accordingly.